Prinsip Mengenali Pengguna Jasa Bagi Notaris Menurut Peraturan Menteri Hukum Dan Hak Asasi Manusia Nomor 9 Tahun 2017 - Marthinus Mesak Mandala (Officium Notarium, 2021)
This research is about the implementation of Permenkumham Number 9 of 2017 related to the principle of recognizing service users for Notaries, and whether Permenkumham Number 9 of 2017 must be followed by Notaries considering the dichotomy of the Notary Position Law. This type of research uses normative legal research (normative juridical). The results of this research conclude that: first, the implementation of Permenkumham Number 9 of 2017 relates to the principle of recognizing service users for Notaries as the provisions of the UUJN only determine the formal requirements by being known/introducing an appearance to a Notary is sufficient to be a requirement for making an authentic deed, and has no responsibility to determine material truth. Second, formally implementing the provisions of Permenkumham Number 9 of 2017 is an obligation for Notaries, but materially if based on the hierarchy theory of laws and regulations it is not an obligation for Notaries to implement Permenkumham Number 9 of 2017, because it is contrary to the Law on Notary PositionsKey Word: Notary, service userAbstrakPenelitian ini tentang implementasi Permenkumham Nomor 9 Tahun 2017 terkait prinsip mengenali pengguna jasa bagi Notaris, dan apakah Permenkumham Nomor 9 Tahun 2017 wajib diikuti oleh Notaris mengingat adanya dikotomi terhadap Undang-Undang Jabatan Notaris. Jenis penelitian ini menggunakan jenis penilitian hukum normatif (yuridis normatif). Hasil penelilitan ini menyimpulkan bahwa: pertama, implementasi Permenkumham Nomor 9 Tahun 2017 berkaitan dengan prinsip mengenali pengguna jasa bagi Notaris sebagaimana ketentuan UUJN hanya menentukan syarat formal dengan dikenal/diperkenalkannya penghadap kepada notaris sudah cukup untuk menjadi syarat pembuatan akta autentik,dan tidak memiliki tanggung jawab untuk menentukan kebenaran materiil. Kedua, secara formal pelaksanaan ketentuan Permenkumham Nomor 9 Tahun 2017 merupakan kewajiban bagi Notaris, namun secara materiil apabila berdasarkan teori hierarki peraturan perundang-undangan bukan merupakan kewajiban bagi Notaris untuk melaksanakan Permenkumham Nomor 9 Tahun 2017,karena bertentangan dengan Undang-Undang Jabatan NotarisKata Kunci: Pengguna Jasa, Notaris